Casein-based Edible Antimicrobial Film Containing Cinnamaldehyde: Physical, Mechanical and Antimicrobial Properties - Mahanta, Snehadri; Singh, Vaishali; Vashisht, Pranav; Gaurav; Mahanta, Shikhadri; Panjagari, Narender Raju; Pradhan, Diwas (Indian Journal of Dairy Science, 2026)
Studies produced composite films of sodium caseinate and cinnamaldehyde (0%, 1.5%, 2.5%, and 3.5%) using a reduced particle emulsion method. Variations in thickness, moisture content, water barrier (COBB test), tensile strength, and bursting strength were evaluated. The antimicrobial effect of each film was observed through the zone of clearance/inhibition against the E. coli K-12. There was a non-significant (p>0.05) and significant (p<0.05) increase in the thickness and moisture content between the control (0%) and cinnamaldehyde-concentrated films, respectively. COBB test values reflected better water barrier properties of cinnamaldehyde films than control. Film with 3.5% cinnamaldehyde concentration had the highest tensile strength but was non-significantly (p>0.05) different from 2.5% film. However, bursting strength was highest for the 2.5% film and was non-significantly (p>0.05) different from the control (0%) film. Antimicrobial testing demonstrated the highest zone of clearance for 2.5%, among all the three concentrations used.